CLASS ATTENDANCE AS A FACTOR AFFECTING ACADEMIC PERFORMANCE - Doniņa, Agita; Svētiņa, Karīna; Svētiņš, Kristaps (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this paper is to investigate whether class attendance in higher education improves academic performance. The research has been performed among bachelor level (EQF 6) international students studying in English for a full-time degree in Latvia.  The attendance is analysed for fall and spring semesters while the academic performance has been analysed in three categories – midterm exam grade, exam grade and the final assessment. Correlation as a research instrument has been applied. The research results reveal interconnectivity between the attendance of classes and the subsequent academic performance.The results of the correlation obtained have been discussed with a representative of Higher Education Export Association.